First report of Vulvovaginitis due to Cryptococcus magnus in Iran - Ali ghajari; Ensieh lotfali; Maryam Norouzi; Zahra Arab-Mazar (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Cryptococcus. magnus is a non-Cryptococcus neoformans species isolated from certain plants, soil, air, and arctic glaciers. Case report: This report describes a case of a 23-year-old Iranian female with pruritus and vaginal irritation. Conventional tests and molecular analysis of the samples of vaginal discharge were performed. The mentioned analyses revealed Cryptococcus magnus as the causative agent of vaginal infection. The minimum inhibitory concentration analysis revealed that this species is susceptible to itraconazole, fluconazole, ketoconazole, and amphotericin B. The patient received 200 mg of oral ketoconazole once daily for 10 days. The patient did not show any clinical signs of vaginal infection after six months. Conclusion: C. magnus was found to have the ability to cause vulvovaginitis. This is the first report of successful detection and treatment of vulvovaginal infection with C. magnus.